Application of Principles and Rules for Non-Cash Transactions Using QRIS Services Maqāṣid Al-Sharīʿah Perspective - Nurul Rahmah Kusuma; Hanif Nuryana (IAIN Syekh Nurjati Cirebon, 2024)
Widespread digital technology and financial technology (fintech) have made non-cash transactions increasingly popular and accepted by society. QRIS (Quick Response Code Indonesian Standard) is a form of non-cash transaction that is expected to increase efficiency, effectiveness, and security in terms of transactions. The research aims to analyze the principles and rules of non-cash transactions using QRIS Services from an Islamic economic perspective so that people can experience non-cash transactions safely while integrating with the ethical values of the Islamic economic system. The research method used is a type of qualitative research with a descriptive analysis approach in the form of a literature study sourced from primary and secondary book sources, consisting of a collection of primary theories and books, journal articles, and various kinds of relevant library materials. The results of this research explain that non-cash transactions using QRIS services are generally by Islamic economic principles, such as fairness, and consent, not containing elements of usury, gharar and maysir, transaction transparency, and halal. However, it should be noted that the use of QRIS must be done wisely and by Sharia corridors.